Collaborative Ethno-STEAM Enriched Project-Based Learning (CoE-STEAM-PjBL): Its Impact On Prospective Science Teachers’ Collaboration And Creative Thinking Skills - Sumarni, Woro; Sumarti, Sri Susilogati Sumarti; Dewi, Siti Herlina Dewi; Imaduddin, Muhammad (Jurnal Pendidikan IPA Indonesia, 2025)
Students’ 21st-century skills, particularly collaboration and creative thinking, remain underdeveloped. Previous studies have introduced the Collaborative Ethno-STEAM Enriched Project-Based Learning (CoE-STEAM-PjBL) model, but its implementation and effects in teacher education settings have not been thoroughly investigated. This study aims to analyze the impact of CoE-STEAM-PjBL on prospective science teachers’ collaboration and creative thinking skills. Using a pre-experimental One-Shot Case Study design, the research was conducted at a teacher education institution. Data were collected through creative thinking tests and collaboration observation sheets. Learning was conducted using the CoE-STEAM-PjBL syntax with product-based projects rooted in local wisdom. The data were analyzed descriptively. Results showed that 29% of participants are highly creative, 48% are creative, and 23% are fairly creative. For collaboration, 17% were in the very good category, 58% good, and 25% moderate. The most prominent indicator of creative thinking was fluency, while social interdependence was dominant in collaboration. Thus, it can be concluded that the implementation of CoE-STEAM-PjBL has an impact on increasing collaboration and creative thinking of prospective teachers. This study contributes to the development of science education by providing empirical evidence on the integration of local wisdom and ethnoscience in STEAM-based project learning to enhance essential 21st-century skills among prospective teachers.